Clinical Evaluation of A Digital vs An Analog Hearing Aid - Nagai, Nobuko; Watanabe, Takahiro; Hayashi, Yasuhiro; Hoshino, Tomoyuki; Iwasaki, Satoshi (AUDIOLOGY JAPAN, 2001)
Differences in performance between the digital hearing aid (Phonax Claro 21dAZ) and analogue hearing aids worn by 9 sensorineural hearing-impaired subjects were evaluated. We used objective measurements (speech discrimination tests in quiet and multitalker noise) and subjective assessments (questionnaires). The subjective scores were better for the digital hearing aid than the analogue hearing aids. Performance in a speech discrimination in noise was also better for the digital hearing aid at the noise level of 75dB when speech level was 70dB, but no statistically significant was found. No difference between the digital and analogue hearing aids could be demonstrated in the objective speech discrimination test in quiet. The results may be interpreted as indicating that the digital hearing aid may be preferred for the noisy environments.